The game of Tejo: A national symbol or an uninished project? - Rodríguez, Gabriel Abello (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper seeks to reclaim an autochthonous Colombian practice: the game of Tejo or “Turmequé”. In the twenties and thirties of the twentieth century, a small sector of the elite class with nationalist and hygienist tendencies, had the intention of using this popular game as a civilizing instrument for working class sectors and transforming it into the national sport of Colombian people. Their purpose was to make sports accessible to all, to generate discipline, and control men and women’s free time.Besides, they had the intention of becoming an identity model for the construction of a national identity.